Penilaian Analitik, Holistik dan Skala Persepsi pada Pelajaran Aljabar - Elva Susanti; Citra Indah Asmarawati; Anggia Arista; Sadiq Ardo Wibowo; Arsyad Sumantika (Lattice Journal : Journal of Mathematics Education and Applied, 2023)
Education is very important for the progress of the country, education cannot be separated from an assessment. Assessment must be based on the existing rubric to be clear, structured, and transparent. One of the existing assessments is based on analytic, holistic, and perceptual scales. The purpose of this study was to establish an assessment rubric in the algebra course because the course was only seen from a quantitative assessment, but in this study, it was assessed based on attitude, and character and then made criteria based on independent assignments and structured assignments and the results would later be tested differently by using the sample t-test. test, namely the independent sample t-test, the results of the data are not normally distributed, it is better to use the Wilxoson test and sign t-test. The result is that there is no difference between independent tasks and structured tasks seen from the significant table and the t-test table. Pendidikan sangatlah penting bagi kemajuan negara, pendidikan tidaklah lepas dari suatu penilaian. Penilaian haruslah berdasarkan rubrik yang ada agar jelas, tertruktur dan transparan. Salah satu penilaian yang ada berdasarkan analitik, holistik dan skala persepsi. Tujuan penelitian ini, menetapkan rubrik penilaian dalam matakuliah aljabar karena matakuliah tersebut hanya dilihat dari penilaian kuantitatif saja, namun dalam penelitian ini dinilai berdasarkan sikap, karakternya juga kemudian membuat kriteria berdasarkan tugas mandiri maupun tugas terstruktur dan hasilnya nanti akan diuji beda dengan menggunakan uji sampel t test yaitu independent sample t test, hasilya data tidak terdistribusi normal sebaiknya menggunakan uji wilxoson dan sign t-test. Hasilnya tidak ada perbedaan antara tugas mandiri maupun tugas terstruktur dilihat dari tabel signifikan maupun tabel t test nya.